Konsep Mesianik dan Apologetik Matius melalui Perumpamaan Mesianik Menurut Matius 21:33-43 - Daniel Lindung Adiatma; Eldad Mesakh Pramono (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2022)
The study of parables in the Synoptic Gospels is a complex process. Matthew 21:33-44 has stated a parable that has the potential to distort the understanding of its readers. The absence of the author's explanation of the meaning of the parable makes the readers understand the parable differently, depending on the reader's point of view. The parable has also generated debate among New Testament scholars. Even evangelical scholars have found no agreement on the meaning of the parable. The purpose of this study is to find a comprehensive theological meaning formulation of the parable that has been recorded in Matthew 21:33-44. This paper presents three analyses that are relevant to understanding the parable of the vineyard cultivators. Historical background analysis, material analysis, and theological analysis are relevant approaches in bridging understanding between the early recipients of parable teachings and the first-century Christians. The parable of the cultivators of the vineyard cannot be interpreted allegorically but in light of the context in which the material is compiled. Apart from providing a strong Christological meaning, this parable is Matthew's apologetic argument to correct the mistake of the Jews in rejecting Jesus and to convince his readers that Jesus is the Messiah that God has promised in the Old Testament.Studi tentang perumpamaan dalam Injil Sinoptik merupakan proses yang rumit. Matius 21:33-44 telah menyatakan suatu perumpamaan yang berpotensi membiaskan pemahaman para pembacanya. Tidak adanya penjelasan penulis terhadap makna perumpamaan menjadikan para pembacanya memahami perumpamaan tersebut secara berbeda, tergantung pada sudut pandang pembaca. Perumpamaan tersebut juga telah menimbulkan perdebatan pada kalangan sarjana Perjanjian Baru. Bahkan para sarjana injili pun tidak menemukan kesepakatan terkait pemaknaan perumpamaan tersebut. Tujuan penelitian ini adalah menemukan suatu rumusan makna teologis yang komprehensif dari perumpamaan yang telah dicatatkan dalam Matius 21:33-44. Tulisan ini memaparkan tiga analisis yang relevan dalam memahami perumpamaan tentang penggarap kebun anggur.  Analisis latar belakang sejarah, analisis materi dan analisis teologi merupakan pendekatan yang relevan dalam menjembatani pemahaman antara penerima ajaran perumpamaan mula-mula dengan orang kristen abad pertama. Perumpamaan tentang penggarap kebun anggur tidak dapat ditafsirkan secara alegoris melainkan dengan mempertimbangkan konteks pengkompilasian materi. Selain memberikan makna kristologis yang kuat, perumpamaan ini merupakan argumentasi apologetis Matius untuk mengoreksi kesalahan orang Yahudi menolak Yesus serta meyakinkan pembacanya bahwa Yesus adalah Mesias yang telah dijanjikan oleh Allah dalam Perjanjian Lama.